2018
DOI: 10.1016/j.ijhydene.2017.12.022
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hydrogen addition on silica aggregate growth in atmospheric-pressure, 1-D methane/air flames with hexamethyldisiloxane admixture

Abstract: The effects of hydrogen addition on silica aggregate growth in atmospheric-pressure, 1-D methane/air flames with hexamethyldisiloxane admixture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The measurements of particle size in the postflame zone were performed by laser light scattering, as described in our previous study [33]; the setup is also shown in Figure 2. In short, a laser beam is directed through the flame, and scattered light is detected at four different angles, .…”
Section: Soot Measurementsmentioning
confidence: 99%
“…The measurements of particle size in the postflame zone were performed by laser light scattering, as described in our previous study [33]; the setup is also shown in Figure 2. In short, a laser beam is directed through the flame, and scattered light is detected at four different angles, .…”
Section: Soot Measurementsmentioning
confidence: 99%